Facebook as a learning environment for language teaching and learning: A critical analysis of the literature from 2010 to 2017. (24th August 2018) - Barrot, Jessie S.
Abstract: The increasing popularity of Facebook has prompted scholars and educators to explore its potentials as a learning environment for various fields of education. Along this line, several reviews of literature have been written about the educational use of Facebook; however, none of them have focused on a specific field of interest such as language pedagogy. Thus, this paper defines the contour of scholarly literature on Facebook as a technology‐enhanced learning environment in language teaching and learning. Using Scopus database as a source, 41 scholarly documents were retrieved and analysed. The demographics of the selected studies show that most of the published research came from Asia and were conducted in the higher education context. In terms of foci of interest, most of the studies focused on developing students' general language proficiency and productive skills. Although a great majority of the studies relied on self‐report data and preexperimental research, the current literature suggests the viability of integrating Facebook into language pedagogy. Suggestions for future studies are discussed. Lay Description: What is currently known about the subject matter: Facebook remains to be the most popular social networking site. A significant number of research have been published about Facebook as a learning environment. Interest in Facebook for educational purposes has been increasing. At least five reviews on Facebook as a learning environment has been published since 2011. What this paper adds: The current study zeroes in on a specific field of study (i.e., language teaching and learning). The current study takes into account studies published between 2010 and 2017. The current study analyses the studies in terms of demographics and foci of interest. The current study attempts to define the contour of scholarly literature on Facebook as a technology‐enhanced learning environment in language teaching and learning. Implications of study findings for practitioners: The findings provide various ways on how Facebook can be implemented for pedagogical purposes. The findings present challenges and issues that need to be confronted for efficient use of Facebook pedagogical affordances. Facebook is a viable tool for technology‐enhanced assessment. Future Facebook‐related studies may embark on underexplored areas of language pedagogy such as teacher cognition, language learning strategies, and development of multiliteracies and pragmatic competence of students.